The effect of pre- and postharvest factors on qualitative attributes, phytochemical properties and incidence of physiological disorders in loquat fruit - Hadjipieri, Margarita (Department of Agricultural Science, Biotechnology and Food Science, Faculty of Geotechnical Science and Environmental Managment, Cyprus University of Technology, 2020)
Loquat (Eriobotrya japonica Lindl.) belongs in the Rosaceae family and Pomoideae subfamily, originated from southwest China. It is a subtropical evergreen fruit tree that blooms in fall and early winter. Its unique reversed annual cycle enables the species to adapt well in the Mediterranean basin and other subtropical climates. Over the recent years the worldwide loquat cultivation has been intensified due to the excellent organoleptic characteristics of the fruit, high nutritional value as well as reduced phytosanitary problems. In Cyprus, the loquat cultivation is mainly favoured in the coastal regions, covered by mesh and/or plastic. „Karantoki‟ and „Morphitiki‟ are the two predominant cultivars. The production is exclusively destined for domestic consumption due to low production volumes that are being produced and the high perishability of the commodity. Loquat commercial production has risen in interest as it has been shifted from a small local cultivation to a niche product that nowadays can gain added value as it is available during late winter- early spring period. In view of the abovementioned actualities, the current dissertation was composed of five independent yet interrelated experiments. The first two fundamental studies dealt with: (1) the analytical and molecular carotenoid profile investigation of loquat fruit during successive on-tree developmental stages and (2) the involvement of polyphenolic (PAL1, PAL2 and PPO1) and carbohydrate (CWI2, CWI3, SPS1, SPS2, NI2, NI3, SuSy, HXK, FRK and VI) biosynthesis transcripts in the incidence of purple spot physiological disorder. In addition, three studies with technological perspectives were employed: (1) the effect of harvesting day on phytochemical attributes, mechanical properties and postharvest performance of loquat fruit, (2) the effect of foliar spray applications [acetylsalicylic acid (ASA), spermidine (Spd), and a commercial calcium supplement] on postharvest performance of loquat fruit and (3) the effect of modified atmosphere packaging on qualitative attributes of loquat fruit after refrigerated storage.
Keywords: Eriobotrya japonica; developmental stages; maturation; ripening; β-carotene; β-cryptoxanthin; lutein; LC-MS; carotenoid biosynthetic pathway; cold storage; chilling; phytochemicals; free phenolics; bound phenolics; antioxidant capacity; purple spot; preharvest disorder; gene expression; sucrose; glucose; fructose; phenolic compound